The Category of Time in English, Russian and French Phraseology - (:unkn) unknown (KARABUK UNIV, 2017)
In the paper we make an attempt to analyze linguistic and cultural descriptions of phraseological units of English, Russian and French reflecting the category of time. In the study of each language about 200 of phraseological units associated with the category of time were taken, which were divided into 5 groups representing different phraseo-semantic concepts. We have carried out a semantic analysis of the data of phraseological units identified by national-cultural peculiarities of expression of time category. The results can be used in the practice of teaching English, Russian and French as foreign languages, in courses on linguistics, and are also taken into account compiling dictionaries.
Keywords: Time; English; Russian; French; Phraseological units